Biocompatibility of Bioceramic Root Canal Sealers: A Review - Ja'apar, Siti Aisyah Nadirah; Ichwan, Solachuddin J. A.; Mustaffa, Musliana (Science University of Malaysia, 2021)
The advantageous technology in endodontics nowadays are bioceramic root canal sealers. The most favourable characteristics of bioceramics root canal sealers are biocompatibility, osteoinductivity and sealing ability. Advantageous characteristics and good bioceramic outcomes make them increasingly presented in the dental market, suitable for use in endodontics. However, the biocompatibility of recently developed bioceramic root canal sealers is not well understood due to the limited scientific evidence and methodological differences in the previous studies. Literature search was conducted from August 2020 until April 2021 through PubMed, Google Scholar and Scopus databases using the combination of terms such as “bioceramic root canal sealers”, “biocompatibility”, “root canal sealer”, “cytotoxicity” and “endodontics” to identify the most relevant articles from year 1991 until 2020. This article aimed to review the bioceramic root canal sealers with regards to the use in endodontics, biocompatibility, and in vivo studies. Bioceramic root canal sealers have a variable toxic potential at the cellular and tissue level, based on the current data. The methodological variability of the studies included in this study, as well as the somewhat contradictory findings, make it impossible to draw a conclusion about which type of bioceramic root canal sealer is more biocompatible. Hence, bioceramic root canal sealers were discovered to be biocompatible and comparable to other commercially available root canal sealers.